Úspěšná terapie české pacientky s ROS1 translokací crizotinibem - Svaton, M; Pešek, M (Klinicka onkologie, 2016)
Targeted therapy of lung cancer has brought significant improvement in prognosis for a lot of patients with EGFR-sensitive mutations and ALK translocations. Other clinical studies have shown ROS1 translocation as another potential target. Our case report brings probably the first successful use of crizotininib in a patient with ROS1 translocation in the Czech Republic. Treatment was well-tolerated and persists continually. During the control PET/ CT scans, partial regression of the disease was observed. ROS1 translocation becomes another promising target for our patients. Therefore, in our opinion, serious discussion about its inclusion among the basic genetic testing in lung adenocarcinomas should occur.
Keywords: Protein-Tyrosine Kinases; tyrosinkinasy; Pyridines; inhibitory proteinkinas; nádory plic; pyrazoly; pyridiny; Proto-Oncogene Proteins; Humans; Pyrazoles; translokace genetická; Crizotinib; Protein Kinase Inhibitors; Translocation, Genetic; krizotinib; Lung Neoplasms; lidé; protoonkogenní proteiny